The effects of age, sex and tenure on the job performance of rubber tappers - Ali, Hassan; Davies, D. Roy (John Wiley & Sons, Inc., 2010)
Data on job performance were collected for 1,053 male (N = 461) and female (N = 592) rubber tappers from nine different estates in Malaysia, and analysed for age, sex and tenure differences.Job performance data were based on output measures derived from production records over a 12-month period. Since the type of terrain varied considerably across plantations, terrain was classified as either ‘hilly’ or ‘undulating’ and the effects of terrain type on performance were also examined.The relationship between age and total output took the form of an inverted U. Partial correlation analyses indicated that tenure, rather than age, was the main determinant of job performance.More experienced rubber tappers were found to perform better than less experienced rubber tappers.Women had significantly higher output levels than did men. Tappers working on estates with predominantly hilly terrains produced significantly higher levels of output than did tappers working on estates with predominantly undulating terrains. Neither sex nor tenure interacted significantly with terrain.These results are discussed in relation to previous research concerned with group differences in job performance.